1998
DOI: 10.3133/pp1587
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment of the San Joaquin-Tulare basins, California: Analysis of available data on nutrients and suspended sediment in surface water, 1972-1990

Abstract: This report is an element of the comprehensive body of information developed as part of the NAWQA Program. The program depends heavily on the advice, cooperation, and information from many Federal, State, interstate, Tribal, and local agencies and the public. The assistance and suggestions of all are greatly appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…During the summer and early autumn when their study took place, higher temperatures and longer travel times from sources favor conversion of dissolved organic nitrogen and ammonium to nitrate. Consistent with these observations, Kratzer and Shelton (1998) reported that about 53% of total nitrogen sources in the drainage basin for the San Joaquin River near Vernalis were of ani-mal origin. The nitrate increase could therefore be due, at least in part, to an increase in animal waste and sewage sources.…”
Section: Discussion Nutrient Management and Phytoplanktonsupporting
confidence: 73%
See 1 more Smart Citation
“…During the summer and early autumn when their study took place, higher temperatures and longer travel times from sources favor conversion of dissolved organic nitrogen and ammonium to nitrate. Consistent with these observations, Kratzer and Shelton (1998) reported that about 53% of total nitrogen sources in the drainage basin for the San Joaquin River near Vernalis were of ani-mal origin. The nitrate increase could therefore be due, at least in part, to an increase in animal waste and sewage sources.…”
Section: Discussion Nutrient Management and Phytoplanktonsupporting
confidence: 73%
“…In any case, the long-term trend for both total N:P ( Figure 6) and inorganic N:P values since 1980 has been in the direction of higher ratios and more susceptibility to phosphorus limitation. Kratzer and Shelton (1998), in their study of [1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990] water quality, noted a long-term increase in nitrate concentration in the San Joaquin River, which they attributed to native soil nitrogen from expanding subsurface agricultural drainage. Other changes possibly affecting the nitrogen and phosphorus balance over time included an increase in aeration of municipal wastewater ponds and land application of domestic wastewater.…”
Section: Discussion Nutrient Management and Phytoplanktonmentioning
confidence: 99%
“…Lehman (2000) recently summarized long-term changes in phytoplankton community composition for the Delta, emphasizing the effects of climatic variability. Kratzer and Shelton (1998) describe nutrient sources and trends in San Joaquin River nutrient levels since the early 1950s. Fertilizer runoff, subsurface agricultural drainage, wastewater treatment plant discharges, and runoff from dairies have contributed to increasing concentrations over the last 50 yr.…”
mentioning
confidence: 99%
“…Ammonium accounts for 20% and presumably dissolved organic matter the remaining 20%. The latter two could be in part extracellular and degradation products of phytoplankton and phytodetritus, but probably originate directly from agricultural sources, including animal wastes (Kratzer and Shelton 1998;Kratzer and others 2004). Insofar as these other sources do not covary with phytoplankton, they are a source of uncertainty in the analyses and models of this study.…”
Section: Causal Factorsmentioning
confidence: 99%
“…Nitrogen from animal wastes leaking directly to surface waters or first volatilizing as ammonia is often the largest single source for estuaries. The San Joaquin River watershed is no different in this respect, with much if not most of the nitrogen originating as animal waste (Kratzer and Shelton 1998;Kratzer and others 2004). The complexity of controlling mechanisms, though, which it shares with other dredged river channels receiving agricultural and wastewater inputs, has stimulated a large amount of diverse monitoring, experimentation, and modeling.…”
Section: Management Scenariosmentioning
confidence: 99%